Rural community perceptions and practices toward the novel coronavirus (COVID-19) prevention in Konso Zone, Southern Ethiopia: a lesson for the next pandemic - Karbana, Gedeno; Ambelu, Argaw; Birke, Wondwossen; Asefa, Lechisa; Lemma, Hailu; Belay, Mekdes Mekonen (Frontiers in Public Health, 2024)
Background Corona Virus Disease (COVID-19) has provided a lesson on preparedness and coping mechanisms for similar pandemics to different community segments. To control and prevent the spreading of COVID-19, people need to possess the correct attitude and perception to follow the appropriate practices against the causative agent. Therefore, this study aimed to assess the rural community's perceptions and practices toward COVID-19 prevention among southern Ethiopia's Konso zone rural communities. Methods A community-based cross-sectional study conducted from April to May 2022 on 605 study participants in the Kena district of the Konso zone of Ethiopia. Participants were recruited using simple random sampling techniques. Face-to-face interviews were conducted to collect data using structured questionnaires developed from the World Health Organization guide and related literature. A logistic regression model was used to identify determinants of perception and practice. Results Among the 564 participants, 296 (52.5%) believed they would go to the healthcare facility if they contracted COVID-19. About 276 (48.9%) perceived that COVID-19 is not a stigma and should not be concealed. About 233 (41.3%) perceived COVID-19 would be controlled. However, the majority, 451 (80%), 440 (78%), 384 (68.1%), 381 (67.6%), 337 (59.8%), and 317 (56.2%) perceived that the cause of COVID-19 is sin, eating some food items were effective against the virus, no cases in their locality, living far away from COVID-19 area, the virus does not exist, respectively. Overall, only 22.5% of the study participants have good perceptions. About 58.5% practiced handwashing to prevent COVID-19, and 45.2% covered their mouth and nose while coughing/sneezing. Among the participants, 39.8% were vaccinated, and about a quarter (24.8%) of the respondents had good prevention practices. Participants with better educational status, use of social media as a source of information, and those with better income levels are found to be protective factors while being married is a risk factor. Conclusion The status of the participant's perception and preventive practices toward COVID-19 was meager. There was a substantial magnitude of wrong perceptions about controlling such pandemics. High inaccurate perceptions and low preventive practice need an urgent and sustained improvement strategy to tackle similar pandemics or epidemics.